Diagnostic Value of Fine Needle Aspiration Cytology (FNAC) in Cervical Lymphadenopathy - Javaid, Muhammad; Ullah, Niamat; Anwar, Khurshid; Said, Muhammad (Journal of Postgraduate Medical Institute, 2011)
the aim of this study was to evaluate the diagnostic value of fine needle aspiration cytology (FNAC) in head and neck lymph nodes and in differentiating malignant from benign disease. This prospective stuy was conducted in the ENT department of HMC, and LRH, Peshawar from first April 2003 to 30th March 2004. A total of 42 patients were studied. After thorough history and examination. FNA biopsy was obtained with the help of experienced cytopatholgoist using 21G needle and the results compared with final histopathological diagnosis. FNAC has been found to be a useful diagnostic tool in the evaluation of patients presenting with neck nodes and should be considered before performeing open biopsy.